2017
DOI: 10.1007/s11255-017-1744-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved cancer-specific free survival and overall free survival in contemporary metastatic prostate cancer patients: a population-based study

Abstract: This population-based study provides the first evidence of improved CSM free survival and OM free survival in patients with de novo mPCa since the introduction of several systemic agents for CRPC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 19 publications
3
33
0
Order By: Relevance
“…The present study also shares limitations of all similar studies that were based on the SEER database and relied on a retrospective data design . Furthermore, despite the large sample size, the current study cohort only represents approximately 30% of the population sample with inherent limitations . Despite having the largest absolute and relative numbers of AAs compared with all previous studies that focused on racial disparities in LND rates, AAs do represent a minority relative to NHWs in the current study (14.5%) .…”
Section: Discussionmentioning
confidence: 82%
“…The present study also shares limitations of all similar studies that were based on the SEER database and relied on a retrospective data design . Furthermore, despite the large sample size, the current study cohort only represents approximately 30% of the population sample with inherent limitations . Despite having the largest absolute and relative numbers of AAs compared with all previous studies that focused on racial disparities in LND rates, AAs do represent a minority relative to NHWs in the current study (14.5%) .…”
Section: Discussionmentioning
confidence: 82%
“…A previous study reported an increase in survival in men with metastatic prostate cancer in Denmark whereas in The Surveillance, Epidemiology and End Results (SEER) cohorts in the US no change in survival had occurred between 1980 and 2008 [24]. A more recent update of the SEER cohort showed a slightly increased survival in men with de novo metastatic prostate cancer [25]. These studies did not include data on PSA and Gleason grade so cancer extent and cancer differentiation could not be assessed, nor was there any indication on use of chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…Isolated bone metastases can be resected surgically and radiation may be effective in controlling symptoms. If the patient is asymptomatic, then observation with repeated radiographs may suffice [6]. The usage of bisphosphonate or RANKL inhibitors should be considered to reduce skeletally related events or fractures.…”
Section: Clinical Presentation and Therapeutic Managementmentioning
confidence: 99%